Production of large 41K Bose-Einstein condensates using D1 gray molasses - Chen, Hao-Ze; Yao, Xing-Can; Wu, Yu-Ping; Liu, Xiang-Pei; Wang, Xiao-Qiong; Wang, Yu-Xuan; Chen, Yu-Ao; Pan, Jian-Wei (Physical review, 2016)
We use D1 gray molasses to achieve Bose-Einstein condensation of a large number of 41K atoms in an optical dipole trap. By combining a specific configuration of a compressed magneto-optical trap with D1 gray molasses, we obtain a cold sample of 2.4×109 atoms with a temperature as low as 42 μK. After magnetically transferring the atoms into the final glass cell, we perform a two-stage evaporative cooling. A condensate with up to 1.2×106 atoms in the lowest Zeeman state |F=1,mF=1⟩ is achieved in the optical dipole trap. Furthermore, we observe two narrow Feshbach resonances in the lowest hyperfine channel, which are in good agreement with theoretical predictions.
Gesehen am 30.04.2020
Im Titel ist "41" in 41K hochgestellt